79.7k views
19 votes
(-4z+1) (5z-2)=

solution plz.​

User Gabriel GM
by
6.1k points

1 Answer

3 votes

Answer:

-20z² + 13z - 2.

Explanation:

hello !

you use the F.O.I.L method to multiply these two. first, you multiply the first terms, which are:

(-4z)(5z) = -20z²

then, the outside terms, which are:

(-4z)(-2) = 8z

then, the inside terms, which are:

(1)(5z) = 5z

then, lastly, the last terms, which are:

(1)(-2) = -2

Therefore, we get:

-20z² + 8z + 5z - 2.

combine like terms, and the answer is:

-20z² + 13z - 2.

User Ramakay
by
6.3k points